Study on the correction of S-N distribution in the welding fatigue analysis method based on the battelle equivalent structural stress by rough set theory - Sun, Yibo (Strojniški vestnik, 2014)
In welding techniques, failure is a key problem that is related to the stability and safety of the welded structure. In the commonly used welding fatigue analysis methods, the Master S-N curve method based on Battelle structural stress solves the problem of inconsistencies in stress calculation and S-N curve selection better than the nominal stress method and hot spot stress method. In this paper, rough set theory was employed to study the S-N distribution based on the Battelle equivalent structural stress. Firstly, rough set analyses of the S-N distribution based on the nominal stress, structure stress and Battelle equivalent structure stress were carried out. Then the S-N distributions based on the three stresses were studied. The results indicated that structural stress rearranges the S-N point making it much more concentrated in the region near the mean S-N curve and that equivalent structural stress places the S-N point more uniformly on both sides of the curve. Subsequently, the corrections from the plate thickness and stress ratio in the Master S-N curve method were studied. It was concluded that with two steps of corrections the decision-making degrees of welding factors are weakened and harmonized in the Battelle equivalent structural stress. This made the S-N distribution much more concentrated and uniform, which allows more accurate welding fatigue prediction by the Master S-N curve.
Keywords: enakovredne napetosti; korekcija; metoda glavne krivulje S-N; porazdelitev podatkov; teorija grobih množic; utrujanje zvarov; varjenje